2012
DOI: 10.1016/j.reml.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Análisis médico-legal de las agresiones a los profesionales sanitarios en Castilla y León (España)

Abstract: La Organización mundial de la Salud (OMS) estima que uno de cada seis trabajadores enferma por maltrato en el ámbito laboral. Uno de los riesgos a los que están sometidos los trabajadores en el desempeño de su actividad diaria es consecuencia de la interacción con otras personas, la cual puede derivar en comportamientos agresivos o de sometimiento o maltrato. No se trata de hechos aislados, que acontezcan alguna vez en un centro hospitalario, sino algo que se repite con demasiada frecuencia en Urgencias y en C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…[4, 7, 46, 47]. In addition, hospitals could impose harsher punishments for committing violence against health workers; this has shown to be an effective deterrent in Spain, where workplace violence rates have reduced [48]. Television campaigns showing that violence against health workers as an intolerable issue also have been successful in reducing violence in England [49] and South Africa [50].…”
Section: Discussionmentioning
confidence: 99%
“…[4, 7, 46, 47]. In addition, hospitals could impose harsher punishments for committing violence against health workers; this has shown to be an effective deterrent in Spain, where workplace violence rates have reduced [48]. Television campaigns showing that violence against health workers as an intolerable issue also have been successful in reducing violence in England [49] and South Africa [50].…”
Section: Discussionmentioning
confidence: 99%
“…In Castilla and Leon, medical professionals (especially physicians) and nursing staff were the most affected by violence directed at them personally followed by attendants and orderlies, although the percentage of affected individuals in each category is not reported. The majority of aggression was verbal (65%) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the aggressions reported to the Medical Association may have a greater severity (Berkson selection bias): one out of every five aggressions had personal injuries and one out of every ten generated a SL and presented material damages. In fact, in other Spanish studies, the reported prevalence of physical damage is lower [ 3 , 8 , 9 , 18 , 19 , 22 ].…”
Section: Main Textmentioning
confidence: 83%